(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article discusses the key aspects of organizing an effective training process for high-level handball players. It covers modern training methods, periodization, physical and tactical preparation, as well as psychological aspects to enhance performance.